Pengaruh E-Modul Sistem Ekskresi Berbasis Guided Inquiry Untuk Meningkatkan Kemampuan Berpikir Kritis dan ICT literasi Siswa SMP N 2 Ngaringan - Nur Laili Miftakhurrohmah; Mohammad Masykuri; Sri Retno Dwi Ariyani Ariyani; M. Noris Noris (Postgraduate, University of Mataram, 2023)
E-Modules are teaching materials that are converted digitally by including images, videos, and animations. E-Modules can be integrated with Model Guided Inquiry. The purpose of the study was to determine the effectiveness of learning using guided inquiry-based E-Modules on students' critical thinking skills and ICT Literacy of students on the subject of the class VII excretion system of SMP 2 Ngaringan. The study population was 207 students of SMP N 2 Ngaringan, Central Java, Indonesia. The research sample used 52 students consisting of 26 students in class VII A and 26 students in class VII B. The results showed that there was a significant effect after giving treatment using Guided inquiry-based E-Modules on students' critical thinking skills and ICT literacy. This is evidenced by the acquisition of Posttest scores for the experimental class ranging from 86.91% on a limited scale and 84.69% on an operational test scale with a high category. The implementation of the syntax of students' critical thinking skills using Inquiry-Based E-Modules has a positive impact on students by increasing the implementation aspects of students' critical thinking skills with an average value of around 96.63% in the high category. The results of the Wilcoxon test at SMP N 2 Ngaringan obtained a sig value. 0.000 <0.05, it can be concluded that the hypothesis H0 is rejected and H1 is accepted. Based on these results, it can be concluded that there is a difference in the average value between before being given a lesson using an E-Module Based on Guided Inquiry and after using an E-Module based on Guided Inquiry on the subject of the human excretory system